1990
DOI: 10.1126/science.2107573
|View full text |Cite
|
Sign up to set email alerts
|

Ribozymes as Potential Anti-HIV-1 Therapeutic Agents

Abstract: Certain RNA molecules, called ribozymes, possess enzymatic, self-cleaving activity. The cleavage reaction is catalytic and no energy source is required. Ribozymes of the "hammerhead" motif were identified in plant RNA pathogens. These ribozymes possess unique secondary (and possibly tertiary) structures critical for their cleavage ability. The present study shows precise cleavage of human immunodeficiency virus type 1 (HIV-1) sequences in a cell-free system by hammerhead ribozymes. In addition to the cell-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
288
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 645 publications
(291 citation statements)
references
References 21 publications
2
288
0
Order By: Relevance
“…[11][12][13][14] In addition, most reports involve targeting viral transcripts, levels of whose expression may be affected by controlling the virus:cell ratio. [19][20][21][22] There are very few reports that demonstrated adequate inhibition of an endogenous cellular transcript -especially one expressed at high levels, and especially in a mixed population of transduced cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] In addition, most reports involve targeting viral transcripts, levels of whose expression may be affected by controlling the virus:cell ratio. [19][20][21][22] There are very few reports that demonstrated adequate inhibition of an endogenous cellular transcript -especially one expressed at high levels, and especially in a mixed population of transduced cells.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Ribozymes have an advantage in the therapy of chronic disease since they are not degraded when the target RNA is cleaved, and therefore, theoretically they need not be produced at higher levels than the target transcript. By using a hammerhead ribozyme, we should be able to target the mutant form of ␣1AT mRNA by using ␣1AT guide sequences attached to the ribozyme catalytic core sequence.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery that certain RNA species possess catalytic activity has generated significant interest in the potential therapeutic use of catalytic RNA molecules (ribozymes) in controlling gene expression (for a review, see Christoffersen & Marr, 1995)+ Ribozymes have been shown to function in trans and can be directed against foreign target sequences by flanking the catalytic core with sequences complementary to the target (Uhlenbeck, 1987;Haseloff & Gerlach, 1988)+ The hammerhead is the smallest of the known ribozyme motifs and therefore amenable to experimental manipulation (for a review, see Symons, 1992)+ Hammerhead ribozymes have broad potential as therapeutic agents for the selective control of gene expression (for a review, see Haseloff & Gerlach, 1988;Sarver et al+, 1990;Christoffersen & Marr, 1995)+ An important problem confronting the use of hammerhead ribozymes as therapeutic agents is that of maximizing the interaction of ribozymes to their target RNAs in vivo+ Experiments employing the unique property of retroviruses to dimerize prior to and during packaging have provided a paradigm for ribozyme-target colocalization (Sullenger & Cech, 1993;Pal et al+, 1998)+ The dimerization and packaging of retroviral RNAs creates a unique physical association of two genomic RNAs+ When a ribozyme is tethered to the dimerization domain, the physical interaction of two dimerization sequences facilitates the base pairing of ribozyme to target+ Physical associations of nonviral RNAs occur within cells, but these usually involve specific base pairing interactions such as snRNAs with splicing signals (Wu & Manley, 1991;Sun & Manley, 1995;Incorvaia & Padgett, 1998)+ The interaction of U1 snRNA with the 59 splice signal has been used as an approach for colocalization of a ribozyme with an HIV target (Michienzi et al+, 1998)+ More subtle methods for ribozyme-target colocalization can take advantage of the properties of some messenger RNAs to be localized within specific subcellular compartments+ The first evidence for cytoplasmic mRNA localization came from the observation that actin tran-scripts are unevenly distributed in ascidian embryos (Jeffery et al+, 1983)+ Subsequently, several maternal mRNAs were identified in Xenopus (Melton, 1987) and Drosophila (Frigerio et al+, 1986) that are localized during oogenesis, and many mRNAs are localized in neurons (Garner et al+, 1988;Burgin et al+, 1990;Tiedge et al+, 1991) and oligodendrocytes (Ainger et al+, 1993)+ Localized mRNAs have also been discovered in somatic cells …”
Section: Introductionmentioning
confidence: 99%
“…These studies have included dominant negative mutants of HIV structural (Gag, 1 Env 2 ) or regulatory (Rev, 3 Tat, 4 PR 5 ) proteins, TAR 6 and RRE 7 RNA decoys molecules for the viral proteins (Tat, REV), antisense RNAs, 8 antibodies directed against Rev, 9 gp120 10 or Tat, 11 and ribozyme designed to cleave at different conserved sites of the HIV-1 genome. 12,13 These approaches all target phases of HIV-1 replication before virus assembly. Alternatively, gp160 proteolytic processing can be inhibited after expression of an ER-retained CD4 chimera in primary human T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant, T-antigen deleted, replication-deficient, SV40-derived vectors deliver stable transgene expression with high efficiency and without selection to cell lines and in primary cell cultures, and in vivo. [24][25][26] rSV40 vectors can be concentrated to high titer (410 12 infectious units (IU)/ml), stably integrate into the host genome, do not require helper viruses, and do not elicit cellular or humoral responses in animals. 27 We delivered native human a 1 AT, a protease inhibitor, to human lymphocyte cell lines and primary human lymphocyte cultures using an rSV40-based vector (SV(AT)).…”
Section: Introductionmentioning
confidence: 99%